Epidemiology of Epizootic Lymphangitis Among Carthorses in Ethiopia - Abdela, Musse G.; Teshale, Sori; Gobena, Mesfin M.; Zewde, Aboma; Jaleta, Hawi; Gumi, Balako; Ameni, Gobena (Frontiers in Veterinary Science, 2021)
Epizootic lymphangitis caused by Histoplasma capsulatum variety farciminosum is a debilitating disease incurring considerable economic losses and affecting the welfare of carthorses. Understanding of its epidemiology is important for devising effective prevention and control measures. A cross-sectional study was conducted on 4162 carthorses in 17 towns in Ethiopia between October 2018 and June 2019 Clinical and microscopic examinations, fungal culturing and polymerase chain reaction were used for undertaking this study. The overall prevalence of epizootic lymphangitis was 16.67% (95 % CI: 15.55 – 17.84) in study carthorses. Epizootic lymphangitis was detected in carthorses found in 16 of the 17 towns included in the study. The highest prevalence was recorded at Kombolcha Town (33.33 %; 95 % CI: 27.54 – 39.52) whereas the lowest was recorded at Debre Birhan Town (0.00 %; 95 % CI: 0.00 – 1.27). The results of univariable firth logistic regression analysis showed that there was no significant difference in the prevalence epizootic lymphangitis among Kombolcha, Holota and Shashemene. Statistically significantly lower prevalence was observed in other towns. Classification of the cases into different clinical forms showed that 87.18 %, 4.33 %, and 0. 58 % were cutaneous, ocular and respiratory forms, respectively while the remaining 7.93 % (55/694; 95 % CI: 6.03 – 10.19) were classified as mixed form. In terms of the severity of the disease, 28.67 %, 60.52 % and 0.81 % were mild, moderate, and severe cases, respectively. The majority of the lesions (43.95 %) were observed in the skin followed by forelimbs (14.55 %) and neck region (14.27 %). The mean annual temperature and annual rainfall of the study towns were statistically significantly associated with occurrence of epizootic lymphangitis. In conclusion this study revealed the wide spread occurrence of epizootic lymphangitis in carthorses in towns included in the present study. The veterinary and livestock authorities should take this into account while devising disease control.